Menerawang kesatuan pengelolaan hutan di era otonomi daerah - Ngakan, P.O.; Komarudin, Heru; Moeliono, M. (Center for International Forestry Research, 2008)
Regulation PP No. 6/2007 on forest administration and management planning re-introduced forest management units, called Kesatuan Pengelolaan Hutan (KPH) intended to ensure the sustainable and efficient management of forest resources. While it offers a promising system for managing forest resources throughout the country, there are still many unanswered questions .How will it be effectively implemented given the increased demand for collaborative and decentralized system; what is the role of local governments in the planning and implementaion of the system; how institutions (rules as well as organization) and shared duties between the newly set up forest unit organization with the existing local forest institutions, will be dealt with. The brief discusses the concept and challenges of the effective adoption of these units (shared authorities between central and local government, re-organization, operational cost and stakeholder’s readiness). The brief concludes that if the forest management unit system is to be implemented it requires (1) rethinking of forest management unit as ecologically based units with multiple functions rather than have separate units for each main functions, and (2) intensive socialisation and working with local stakeholders. The establishment of the organization of the units should also consider the whole institutional restructuring and take account of aspirations of stakeholders who are involved from the planning to implementation phase.